Prosopis farcta Seeds: Potential Source of Protein and Unsaturated Fatty Acids?. (20th May 2015) - Lajnef, Houda Ben; Mejri, Houda; Feriani, Anouer; Khemiri, Sheyma; Saadaoui, Ezzeddine; Nasri, Nizar; Tlili, Nizar
Abstract: The goal of this study is to evaluate the chemical composition of the Prosopis farcta seeds. The Kjeldahl method revealed that the level of the total protein was ca. 18 % on a dry weight basis (DW). Gas chromatographic analysis revealed the presence of six fatty acids. Linoleic acid with 57.55 % was the major fatty acid, followed by oleic and palmitic acids (24.58 and 12.91 %, respectively). Total phenolic content was 1.71 mg GAE/g DW (GAE = gallic acid equivalents). Methanolic extracts showed important antioxidant properties. This work highlights the importance of P. farcta seeds as natural and inexpensive sources of protein, unsaturated fatty acid, and phenolic compounds for both cosmetic and pharmaceutical uses.